Development of a Bidimensional Simpatía Scale for Use With Mexican American, Puerto Rican, and Cuban American Adults. Issue 5 (September 2019) - Davis, Rachel E.; Lee, Sunghee; Johnson, Timothy P.; Rothschild, Steven K.
Abstract : Background: Through its influence on social interactions, simpatía may have a wide-ranging influence on Latinx health. Simpatía —which does not have a direct English translation—refers to being perceived as likeable, pleasant, and easygoing. Research to investigate the influence simpatía on Latinx health is limited, likely due to a lack of options for measuring simpatía among diverse Latinx populations. Objectives: The goal of this research was to develop a bilingual, survey-based simpatía scale for use among ethnically diverse Latinx adults in health-related settings. Methods: Data were obtained through a telephone survey data of 1, 296 Mexican American, Puerto Rican, and Cuban American adults living in the United States. Interviews were conducted in English and Spanish. Exploratory factor analysis, item response theory analysis, confirmatory factor analysis, and computation of estimates of internal consistency reliability were conducted to inform the development of the final simpatía scale. Results: Results indicate that the final, nine-item, simpatía scale has high internal consistency (α = .83) and measurement invariance among Mexican American, Puerto Rican, and Cuban American adults. Two dimensions were identified, as indicated by a perceptions subscale and a behavior subscale. Cuban Americans were found to have the highest simpatía scores, followed by Puerto Ricans and Mexican Americans. Discussion: Culture is often identified as a powerful potential influence on health-related behaviors, but measures are often not available to assess specific cultural traits. By developing a new tool for measuring simpatía, this research advances opportunities for understanding and promoting Latinx health.